Growth Stimulation of Tropical Grass (Megathyrsus maximus Jacq.) by Humic Substances and Herbaspirillum seropedicae - Luciano P. Canellas; Natália A. Canellas; Rakiely M. Silva; Etelvino H. Novotny; Fabio L. Olivares (Agronomy)
This study aimed to evaluate the effect of soluble humic substances and plant-growth-promoting bacteria on the vegetative growth of Mombaça grass. A greenhouse experiment was conducted to study the effects of foliar applications of humic substances (0, 12, 24, 48, and 96 mg C L−1) on the growth of Mombaça fifteen days after germination. After determining the optimal concentration range, a field trial was carried out in which humic substances at the best concentration were applied simultaneously with Herbaspirillum seropedicae strain UENF-H19 fifteen days after germination in three replicates. The best growth of Mombaça in the greenhouse was obtained with 48 mg C of the humic substance L−1, which promoted a shoot fresh weight 80% higher than in the control treatment. The increase was almost identical to that observed during the 50-week field experiment in plots treated with humic substances combined with H. seropedicae. The treated plants produced an 81% higher shoot fresh weight than the control, with no dry mass, nitrogen content, or crude protein change during the one-year evaluation period. Despite the efficiency of the selected microbial inoculants under controlled-environment experiments, the agronomical significance under field conditions remains a subject of debate and improvement. The present study demonstrates that combining Herbaspirillum seropedicae with humic substances (plural) could significantly increase pasture production under field conditions.